2016
DOI: 10.1016/j.rmed.2016.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Non CF-bronchiectasis: Aetiologic approach, clinical, radiological, microbiological and functional profile in 277 patients

Abstract: Data indicate that in Greece, "past" tuberculosis remains an important cause of bronchiectasis. P. aeruginosa was the predominant pathogen in the airways, associated with disease severity, while the most common lung function impairment was obstruction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
44
4
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(81 citation statements)
references
References 41 publications
(45 reference statements)
18
44
4
3
Order By: Relevance
“…Patients with P. aeruginosa had more long-standing disease and worsened lung function. [8] Our study had shown concurrence with the previous studies in regard to the decline in FEV1 in patients colonized with Pseudomonas aeruginosa with p value <0.01. It must be underlined that the intensification of anti Pseudomonas aeruginosa antibiotic treatment in these patients (eg, with increased doses, longer treatment, or combined therapy) possibly could slower even stop the impairment of lung function over the longer term.…”
Section: Fev1 Comparison With Microbiological Isolatessupporting
confidence: 92%
See 1 more Smart Citation
“…Patients with P. aeruginosa had more long-standing disease and worsened lung function. [8] Our study had shown concurrence with the previous studies in regard to the decline in FEV1 in patients colonized with Pseudomonas aeruginosa with p value <0.01. It must be underlined that the intensification of anti Pseudomonas aeruginosa antibiotic treatment in these patients (eg, with increased doses, longer treatment, or combined therapy) possibly could slower even stop the impairment of lung function over the longer term.…”
Section: Fev1 Comparison With Microbiological Isolatessupporting
confidence: 92%
“…[7] Dimakou et al had shown that pseudomonas aeruginosa was the most common pathogen yielded in sputum cultures (43%) followed by haemophilus influenza (12.6%). [8] Our study showed a significant percentage of aerobic bacterial colonization and the commonest organism is Pseudomonas aeruginosa followed by klebsiella Pneumoniae. This result was similar to the studies of HUO Hai-yan et al, Dimakou et al and Ho et al However the present study did not show anaerobic organisms in post TB bronchiectasis patients as anaerobic bacteriological culture techniques were not available in our institution.…”
Section: Resultsmentioning
confidence: 58%
“…10,12,20 In a study evaluating the prevalence of bronchiectasis in asthma according to oral steroid requirement, bronchiectasis was found in 20% in the steroid depended group and only 4% in the nonsteroid depended group. 23,24 In the present study, bronchiectasis was found in 67.5% out of 40 severe asthmatic patients evaluated prospectively and rigorously examined for the identification of other aetiological factors. 13 However, other causes of bronchiectasis were not investigated.…”
Section: Discussionmentioning
confidence: 73%
“…Studies from the UK's North East (n = 189) illustrate that occurrence of idiopathic bronchiectasis is high and that those identified with post-infective aetiology developed the condition earlier in life [28]. In contrast, a Greek study (n = 277) demonstrated that prior tuberculosis, pertussis, measles and pneumonia were the leading causes of bronchiectasis [45]. A retrospective study from Nice in southern France (n = 311) similarly described high rates of post-infectious (mainly post-tuberculous) bronchiectasis [29].…”
Section: Bronchiectasis In Europementioning
confidence: 99%
“…Pseudomonas aeruginosa and H. influenzae are the most common bacteria detected in bronchiectasis airways globally although proportions vary among the different populations [45,64]. Other bacterial genera described in bronchiectasis airways include Streptococcus, Prevotella, Veillonella and Staphylococcus [65][66][67].…”
Section: Geographic Variation In the Microbiology Of Bronchiectasis Tmentioning
confidence: 99%